2015
DOI: 10.20867/thm.21.2.5
|View full text |Cite
|
Sign up to set email alerts
|

Students' use of social media during the travel process

Abstract: Purpose -The purpose of the study is to explore how students as an important travel segment are involved in social media during the travel process and explore the underlying dimensions of social media use by students during the travel process. Design/methodology/approach -The quantitative research focuses on the students' use of social media in the three phrases of the travel process -before travel, during travel and after travel separately. Survey instrument was a structured questionnaire. Data were collected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 30 publications
0
5
0
1
Order By: Relevance
“…Nemec Rudež and Vodeb (2015) tried to understand Croatian students' information search on social media for a trip. They found that before the trip, social media usage has two goals: searching for opinions and gathering information for comparison.…”
Section: Literature Review 21 Information Gathering Of Younger Generations In Tourismmentioning
confidence: 99%
“…Nemec Rudež and Vodeb (2015) tried to understand Croatian students' information search on social media for a trip. They found that before the trip, social media usage has two goals: searching for opinions and gathering information for comparison.…”
Section: Literature Review 21 Information Gathering Of Younger Generations In Tourismmentioning
confidence: 99%
“…Uporaba družbenih omrežij za potovanja v tujino je za milenijce pomembna (VisitScotland, 2017), do podobnih ugotovitev so prišli tudi pri ameriških (Barnes in Lescault, 2011), avstrijskih (Zehrer in Grabmüller, 2012 in hrvaških študentih (Nemec Rudež in Vodeb, 2015). S pomenom digitalnih rešitev za generacijo milenijcev se ukvarjajo tudi novejše raziskave raziskovalcev, kot so Pencarelli idr.…”
Section: Spremenjeni Ciljni Trgi In Digitalne Rešitve V Turizmuunclassified
“…It was observed that the young are independent (Desai, Lele, 2017), they expect quick and full access to information and they expect immediate answers to their questions (Opis, Cenusa, 2017). They are heavy users of the internet and the internet-related tools needed for tourism which have been the subject of numerous analyses (Hamed, 2017;Ip, Lee, Law, 2012;Nemec Rudež, Vodeb, 2015).…”
Section: Introductionmentioning
confidence: 99%